2015
DOI: 10.1007/s00170-015-7979-0
|View full text |Cite
|
Sign up to set email alerts
|

A sustainable modular product design approach with key components and uncertain end-of-life strategy consideration

Abstract: Today, sustainability emphasis is imperative for modern design and manufacturing enterprises; therefore, sustainability assessment has attracted increasing attention. In this study, we use cost, environmental impact, and labor time as indicators to measure a comprehensive set of sustainability dimensions: economic, environmental, and social sustainability. Similarly, modular product design (MPD), due to its benefits to design and manufacturing, has been widely accepted as a useful strategy. The need for custom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 50 publications
(30 citation statements)
references
References 62 publications
0
27
0
3
Order By: Relevance
“…Chung et al showed that optimized modular architecture can reduce the overall life cycle cost and other environmental impacts in supply chains, including the carbon footprint . Ma and Kremer introduced modular system design methods to improve the sustainability of the system throughout its total life cycle. Works by Asadi et al and Suh et al focused on modular system design to improve various aspects of the system flexibility.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Chung et al showed that optimized modular architecture can reduce the overall life cycle cost and other environmental impacts in supply chains, including the carbon footprint . Ma and Kremer introduced modular system design methods to improve the sustainability of the system throughout its total life cycle. Works by Asadi et al and Suh et al focused on modular system design to improve various aspects of the system flexibility.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Heat (H) 6,8,9,10,16,17,18,23,30,31,32 Specified components are heat-generating components and need to be assigned to separate modules if possible Maintenance (M) 1 day 1,19,33 Specified components require thorough inspection every 3, 5, or 6 years. Components that require daily maintenance are inspected every day.…”
Section: Design Constraints Affected Components (As Shown In Figure 2mentioning
confidence: 99%
“…MPD principles may have potential to be implemented for example in rooms, units or technical systems while designing hospital retrofits. (Ulrich 1993;Ma and Kremer 2016). Ulrich (1993) described modularity as a form of product architecture, which comprises physical components that enable the function of the product.…”
Section: Modular Product Designmentioning
confidence: 99%
“…De Blok et al (2014) studied the definition of interfaces, which has been found vague in service modularity by other researchers as well (Eissens- Van der Laan et al 2016;Ma and Kremer 2016). Interfaces play a key role in the value provided by modular products or services, as they prescribe how different components of the system mutually interact.…”
Section: Figure 12 Service Modularity Types (Eissens-van Der Laan Etmentioning
confidence: 99%
See 1 more Smart Citation